Treatment and Education on Prevention of Capitis Pediculosis in Female student Pesantren Al-Muslimun at Village Muda Setia, Bandar Seikijang, Pelalawan Regency, Riau - Esy Maryanti; Lilly Haslinda; Firdaus; Mislindawati; Azzuhara (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
Pediculosis capitis is a disease caused by head lice infestation (Pediculus humanus capitis). This disease is often overlooked because it does not cause fatal symptoms but can interfere concentration and activities of the affected individual. Infestation of parasite often affects a group of children in an orphanage, dormitory or boarding school. The purpose of this activity is to carried out at the Al-Muslimun Islamic Boarding School in Muda Setia Village, Bandar Seikijang District, Pelalawan, Riau Province. The target audience is students of tsanawiyah totaling 178 students. On examination, 93% were positive for pediculosis capitis. The students were given treatment of permethrin 1% and counseling in the form education on how to prevent and eradicate the disease. In addition to students, education is also given to musyrifah. It is hoped that students who have received treatment and education can receive and apply the knowledge gained so that can eradicate the disease.